A new methodology for polyvalent intravenous immunoglobulin solution production with a two-stage process of viral inactivation - Antônio Edson de Souza Lucena; Divaldo de Almeida Sampaio; Ednaldo Rosas da Silva; Virgínia Florêncio de Paiva; Ana Cláudia Santiago; Ana Cristina Lima Leite (Universidade de São Paulo, 2010)
Highly purified intravenous immunoglobulin G concentrate (IV IgG) was produced with the use of polyethylene glycol associated to a single-stage precipitation by ethanol, instead of the classic Cohn-Oncley process, which employs cold alcohol as the precipitating agent, in a three-stage process. Precipitation of crude fraction containing more than 95% of immunoglobulin G was performed by liquid chromatography with a cation exchanger, CM-Sepharose, as a stationary phase. During the process, the product was subjected to two-stage viral inactivation. The first stage was performed by the action of sodium caprylate, 30 mM at pH 5.1+/- 0.1, and the second stage was performed by the action of a solvent-detergent mixture. The finished product was formulated at 5% with 10% sucralose as the stabilizing agent. The process yields 3.3g of IgG/liter of plasma. The finished product analysis showed an anti-complementary activity lower than 1CH50. Polymer and aggregate percent levels were lower than 3% in the five batches studied. The analysis of neutralizing capacity showed the presence of antibacterial and antiviral antibodies in at least three times higher concentrations than the levels found in source plasma. The finished product fulfilled all purity requirements stated in the 4th edition of the European pharmacopeia. Obteve-se concentrado de imunoglobulina G intravenosa IgGIV, altamente purificado, utilizando-se polietilenoglicol associado a uma única etapa de precipitação por etanol, em substituição ao tradicional método descrito por Cohn-Oncley, que emprega, em três etapas, o mesmo álcool resfriado, como agente precipitante. A purificação da fração bruta contendo mais de 95% de imunoglobulina G foi realizada utilizando-se cromatografia líquida com um trocador de cátion, a CM-Sepharose, como fase estacionária. Durante o processamento o produto foi submetido a dupla inativação viral sendo a primeira pela ação do caprilato de sódio, 30 mM a pH 5,1+/- 0,1 e a segunda por ação de mistura de solvente/detergente. O produto acabado foi formulado a 5% utilizando-se sucralose 10% como estabilizante. O rendimento da metodologia foi de 3,3g de IgG/litro de plasma. A análise do produto acabado demonstrou atividade anti-complementar inferior a 1CH50. O valor percentual de polímeros e agregados em cinco lotes realizados foi inferior a 3%. O estudo da capacidade de neutralização demonstrou a presença de anticorpos anti-bacterianos e anti-virais em concentração pelo menos três vezes maior que o plasma de origem. O produto acabado apresentou conformidade com todos os requisitos de pureza dispostos na farmacopéia européia IV edição.